Lucifensins, the Insect Defensins of Biomedical Importance: The Story behind Maggot Therapy - Václav Čeřovský; Robert Bém (MDPI AG, 2014)
Defensins are the most widespread antimicrobial peptides characterised in insects. These cyclic peptides, 4-6 kDa in size, are folded into α-helical/β-sheet mixed structures and have a common conserved motif of three intramolecular disulfide bridges with a Cys1-Cys4, Cys2-Cys5 and Cys3-Cys6 connectivity. They have the ability to kill especially Gram-positive bacteria and some fungi, but Gram-negative bacteria are more resistant against them. Among them are the medicinally important compounds lucifensin and lucifensin II, which have recently been identified in the medicinal larvae of the blowflies Lucilia sericata and Lucilia cuprina, respectively. These defensins contribute to wound healing during a procedure known as maggot debridement therapy (MDT) which is routinely used at hospitals worldwide. Here we discuss the decades-long story of the effort to isolate and characterise these two defensins from the bodies of medicinal larvae or from their secretions/excretions. Furthermore, our previous studies showed that the free-range larvae of L. sericata acutely eliminated most of the Gram-positive strains of bacteria and some Gram-negative strains in patients with infected diabetic foot ulcers, but MDT was ineffective during the healing of wounds infected with Pseudomonas sp. and Acinetobacter sp. The bactericidal role of lucifensins secreted into the infected wound by larvae during MDT and its ability to enhance host immunity by functioning as immunomodulator is also discussed.